A Course or a Pathway? Addressing French as a Second Language Teacher Recruitment and Retention in Canadian BEd Programs - Smith, Cameron; Masson, Mimi; Spiliotopoulos, Valia; Kristmanson, Paula (Canadian Journal of Education / Revue canadienne de l'éducation)

(untitled) (Canadian Society for the Study of Education, 2023)
Institutions strive to offer programs that address both the needs of the educational system and incorporate current pedagogical research. Creating a program that is relevant, inspiring, and accessible to aspiring French as a Second Language (FSL) teachers, while also equipping them with the skills and knowledge deemed necessary by the education system, is a delicate balancing act. This study reviewed 44 FSL teacher education programs that lead to professional certification across Canada. Environmental scans drew information from the program websites related to admission requirements, program structure and content, practicum, and graduation criteria. Follow-up interviews with program stakeholders were conducted to verify or clarify the data. The results highlight the inconsistencies that exist among programs for developing FSL educators. We position the ways in which Canadian faculties of education might provide a more holistic “pathway” approach to recruiting, preparing, and retaining emerging FSL teachers.